(untitled) (Brazilian Journal of Health Research, 2024)
Introduction: Violence is an important public health problem that stands out in certain vulnerable groups, and it is necessary to better identify its characteristics for the effectiveness of preventive actions. Objectives: To characterize the reported cases of violence against vulnerable groups in Espírito Santo, from 2011 to 2018. Methods: A descriptive study was carried out, using all cases of violence recorded in the National System of Notifiable Diseases. The variables analyzed included characteristics of the victim, the aggressor and the event. The project was approved by the ethics committee and the analyzes performed in Stata 14.1. Results: The frequency of reporting violence against vulnerable groups was 88.5% (95%CI: 88.1-88.8). Violence against children, adolescents, women and the elderly was mostly committed by men. The victims were mainly brown/black, without disabilities or disorders and residents of the urban/periurban area, and female. Violence is most commonly practiced in homes and is repetitive. Conclusion: Violence is present throughout the life cycle, and actions to face this problem are essential.